PELAJARAN SISTEM PERSON PADA MATA KULIAH RIAS PENGANTIN YOGYA PAES AGENG DENGAN MENGGUNAKAN PRING LANTIP - Yuwati, Herina; Warsihapsari, Tri (Akademi Kesejahteraan Sosial AKK Yogyakarta, 2023)
The aim of this research is to determine the development of the person system learning in the Yogya Paes Ageng bridal make-up course using the pring lantip tool. This research is classroom action research or classroom action research. Data collection uses interview techniques, questionnaires, observation and documentation. Interviews, questionnaires and observations were used to obtain detailed data about the use of Pring lantip in making bridal paes, while documentation was used to describe the results of students' practice in making bridal paes. The data is a qualitative and quantitative description. The classroom action research method states that in general there are four stages in it, namely: 1) Planning, 2) Implementation, 3) Observation, 4) Reflection.The subjects of this research were 23 fourth semester students of the Cosmetology Study Program, the committee showed that (1) learning the person system for students made students understand and pay more attention, (2) learning the person system for Paes Ageng bridal make-up was better and more easily accepted by students, (3) by using the lantip pring tool in the Paes Ageng bridal make-up course with a person learning system, the results are better, the shape of the paes is more perfect, and it is easier for students to use and make the paes